The effect of work from home toward work-life balance and productivity with work stress as a mediating variable: Study on employees of Financial Services Authority (OJK RI) - Subari, Rizki Vina Yurinta; Sawitri, Hunik Sri Runing (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2022)
The Financial Services Authority (OJK) has proposed a policy for employees dealing with the Covid-19 pandemic situation since 2020 in the form of a circular containing a work from home policy in order to prevent and control Covid-19 spread at OJK, which was later replaced with Guidelines for Working in the Adaptation Period “New Habits for Employees in OJK”. This policy requires employees to work from home while still paying attention to work-life balance and producing the same high performance as working in an office. The purpose of this study is to fill the gap in investigating potential factors of employee productivity while working from home since the Covid-19 pandemic such as work-life balance and work stress. This study uses a quantitative method with a Structural Equation Modelling (SEM) and using AMOS application tools. The research sample was 360 respondents with positions ranging from administrative level to Deputy Director in all work units at OJK. The results of this study reveal that working from home, work-life balance, and work stress have a significant influence, either directly or indirectly, on productivity of employees.